Impact of sarcopenia on the future liver remnant growth after portal vein embolization and associating liver partition and portal vein ligation for staged hepatectomy in patients with liver cancer: A systematic review - Wang, Qiang; Wang, Anrong; Li, Zhen; Sparrelid, Ernesto; Brismar, Torkel B. (Frontiers in Oncology, 2022)
Purpose: The impact of sarcopenia on the future liver remnant (FLR) growth after portal vein occlusion, including portal vein embolization (PVE) and associating liver partition and portal vein ligation for staged hepatectomy (ALPPS) has gained increasing interest. This systematic review aimed to explore whether sarcopenia was associated with insufficient FLR growth after PVE/ALPPS stage-1. Methods: A systematic literature search was performed in PubMed, Embase, Web of Science, and Cochrane Library up to 05 July 2022. Studies evaluating the influence of sarcopenia on FLR growth after PVE/ALPPS stage-1 in patients with liver cancer were included. A predefined table was used to extract information including the study and patient characteristics, sarcopenia measurement, FLR growth, post-treatment complications and post-hepatectomy liver failure, resection rate. Research quality was evaluated by the Newcastle-Ottawa Scale. Results: Five studies consisting of 609 patients were included in this study, with a sample size ranging from 42 to 306 (median: 90). Only one study was multicenter research. The incidence of sarcopenia differed from 40% to 67% (median: 63%). Skeletal muscle index based on pretreatment computed tomography was the commonly used parameter for sarcopenia evaluation. All included studies showed that sarcopenia impaired the FLR growth after PVE/ALPPS stage-1. However, the association between sarcopenia and post-treatment complications, post-hepatectomy liver failure, and resection rate remains unclear. All studies showed moderate-to-high quality. Conclusions: Sarcopenia seems to be prevalent in patients undergoing PVE/ALPPS and may be a risk factor for impaired liver growth after PVE/ALPPS stage-1 according to currently limited evidence.